Uma Ferramenta para Organização Semântica de Informações de Helpdesk por meio de Modelagem de Tópicos - Carvalho, Daniel; Pereira, Antônio; Cunha, Washington; Tuler, Elisa; Dias, Diego; Rocha, Leonardo (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2025.13896, 2025)
In this work, we propose a semantic organization tool for textual data applied to enhance the automated analysis of helpdesk tickets (service requests) in large volumes of data. It leverages Topic Modeling (TM) techniques (i.e., CluWords) and Large Language Models (LLMs) to identify recurring patterns and themes (Llama3), aiming to improve categorization and service efficiency. Through a case study with more than 9,000 tickets, we demonstrate its application in real-world scenarios, supporting team sizing, monitoring of emerging demands, and time consumption analysis. The results indicate greater analytical efficiency and decision-making support with the use of the tool.